Solving the problem of stationary heat distribution in a complex cylindrical structure by the finite element method: Solving the problem of stationary heat distribution in a complex cylindrical structure by the finite element method - Polatov, Askhad; Sapayev, Shikhnazar (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
The distribution of the temperature field of elements of three-dimensional structures is examined in the article and the effect of non-homogeneities on the temperature field in three-dimensional axisymmetric structures is studied. Based on the variational statement of the problem, a finite element model for solving axisymmetric problems of heat distribution in three-dimensional bodies was built based on the finite element method (FEM); a computational algorithm of the solution and the software were implemented.